(untitled) (Studia Archaeologica, 2023)
In the recent years intensive archaeological research was done in the Darkhad depression of Northern Mongolia, yielding significant discoveries from the Mongol period, particularly noble burials. Despite rampant looting, several archaeological endeavors have successfully rescued and preserved a substantial number of crucial artifacts. The ongoing research aims to determine the design technology, purpose, and contextual significance of these artifacts, examining the stone mounded tombs of the Mongol period across a wide geographical scope and analyzing the unique characteristics of each local region. This article presents preliminary findings from the study, focusing on the Mongol tombs at the Dood Tsahir mountain within the territory of Renchinlkhumbe Sum, Khuvsgul aimag, located approximately 30 km northeast of the Khorig Mountain. Despite the challenges posed by aggressive looting, the archaeological efforts have not only salvaged important artifacts but also initiated a new chapter in our understanding of the Mongol period in Northern Mongolia. Доод Цахир уулын Монголын эзэнт гүрний үеийн оршуулгын газар Товчлол. Монгол орны умард бүс нутаг Дархадын хотгорт сүүлийн жилүүдэд археологийн судалгаа эрчимтэй хийгдэж, эндээс Монголын үеийн булш оршуулгын, тэр дундаа язгууртны булшинд хамаарах дурсгалууд илэрсэн нь энэ чиглэлийн судалгаанд “шинэ хуудас” нээсэн чухал үйл явдал болсон юм. Эндхийн булшийг тонуулчид толгой дараалан тоносон хэдий ч хэд хэдэн удаа явуулсан авран хамгаалах судалгааны үр дүнгээр олон тооны эд өлгийн олон зүйл илэрсэн ба тэдгээрийн заримынх нь хийц технологи, үүрэг зориулалтыг тодорхойлох, цаашлаад монголын үеийн чулуун дараастай булшны байршлыг өргөн хүрээнд харах, бүс нутгийн хүрээнд онцлог байдлыг нь тодорхойлох зэрэг асуудлыг авч үзэх шаардлагатайг харуулдаг. Энэ удаа Хориг уулаас зүүн хойш 30-аад км зайд байрлах Доод Цахир уулын бүлэг булшны судалгааны урьдчилсан үр дүн, энэ бүс нутгийн монгол булшны онцлогийн талаар өгүүлэв.